Mendaratkan Etika Kerajaan Allah Melalui Falsafah Sitou Timou Tumou Tou Di Suku Minahasa - Wantalangi, Regen; Duryadi, Martinus; Sutrisno, Gideon (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
Abstract Asian Christian theology has been influenced by Western traditions, the power given to them by Christ has been misused, they reconstruct Asian culture, they give new names, they control it, so that Asian people are alienated from their own culture, including the Minahasa tribe. The task of this research is to establish ethics of the kingdom of God through the philosophy of sitou tomu tumou tou in the Minahasa tribe. The research method used is a qualitative research method with a literature study approach. Based on the study, this research found that through the philosophy of sitou timou tumou tou and through Kingdom Ethics, the moral ambivalence of the Minahasa tribe was overcome, which on the one hand demanded Christian faith and on the other hand demanded cultural beliefs, thereby building a bridge in the form of contextual theology between the Bible. and culture in the Minahasa tribe.